Pengaruh Paket "Avil-PMS" terhadap Pengetahuan Remaja Putri di SMA "X" Kota Bandung - Clara Yolanda; R. Nety Rustikayanti; Metha Dwi Tamara (Sehat MasadaJurnal, 2018)
About 7 until 10 days before the onset of menstruation, a young women will have a symptoms of physical or emotional changes known as Pre-menstrual Syndrome (PMS). Knowledge of Pre-menstrual Syndrome should already be known by young women. Giving knowledge can be done with health education by using Audiovisual leaflet pre-menstrual syndrom (AViL-PMS) as a media. This media is more interesting and effective because it involves two senses that is vision and hearing, so it can maximize the acceptance of information. This study aims to determine the influence of AViL-PMS health education about Pre-menstrual Syndrome (PMS) toward the knowledge of young women. This research is quantitative with quasi experimental study design. Sampling using purposive sampling with 42 respondents. Data collection using questionnaires, and data analysis technique using dependent T-test. The results indicate there is an influence of AViL-PMS toward the knowledge (p-value 0,000 < Î± = 0,005). Suggestions in this study for teachers and health workers to cooperate in providing health education on the importance of reproductive health, especially for young women.